Evaluasi Pengalaman Pengguna pada Mahasiswa SAP Fakultas Ilmu Komputer Universitas Brawijaya terhadap Penggunaan Sistem Informasi Akademik menggunakan UX Curve (Studi Kasus: Sistem Informasi Akademik Mahasiswa Universitas Brawijaya) - Taufiqurrachman Ilham; Diah Priharsari; Issa Arwani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Universitas Brawijaya has a website-based application system, namely Sistem Informasi Akademik Mahasiswa Universitas Brawijaya (SIAM UB). SIAM UB serves to fulfill academic and financial services for students of Brawijaya University. In this study aims to produce user experience evaluation documentation in SAP students Faculty of Computer Science during the use of SIAM UB by being evaluated using UX Curve whose assessment is combined with the construction of the UTAUT (Unified Theory of Acceptance and Use of Technology) model. There are 3 aspects of assessment from the UTAUT model as a reference for evaluation in this study, including performance expectancy, effort expectancy and facilitating condition. The number of respondents in this study amounted to 10 SAP students of the Faculty of Computer Science and produced 30 curves along with 189 descriptions of reasons for the curve change. The results from the analysis showed that the aspect of performance expectancy is the aspect that most affects the user experience, which has the highest number of improving curves with 8 curves along with a description of the reason for the curve change which is divided into 55 positive comments and 43 negative comments. Overall, analysis of the results from evaluation for user experience at SIAM UB using UX Curve produces a good impression where it is in line with the average curve of every aspect that is improving the user experience.